THE GOD BEYOND HUMAN FRONTIERS - George Kaniarakath (Journal of Dharma, 2012)
At the beginning of salvation history, when Abraham was chosen as God’s agent of salvation, he was told: “And by you all the families of the earth shall bless themselves” (Genesis 12:3b). Jesus who came as the good shepherd seeking the lost sheep was often found in the ‘bad’ company of tax collectors and others, who were branded as sinners, not to share in their way of life, but to win them to the right path. And it happened that once as Jesus was in the house of Matthew the tax collector and his friends, the Pharisees who considered themselves to be the custodians of the Law wondered and asked the disciples of Jesus why, he being a teacher of the Law, ate with the tax collectors and sinners. Jesus replied, “Those who are well have no need of a physician, but those who are sick” (Matthew 9:12). In the First Testament we have the prophetic books of Jonah, Amos, Second Isaiah and Malachi which are revolutionary in the understanding of God’s attitude toward the wicked and the other nations. In this essay we look at these books from these perspectives which are crucial in a world of multicultural and multi-religious dimensions.